A meta-analysis of Chikungunya virus in neurological disorders - da Costa, Vivaldo G. [UNESP]; Saivish, Marielena V.; Sinhorini, Paola F. [UNESP]; Nogueira, Maurício L.; Rahal, Paula [UNESP] (Elsevier, 2024)
Chikungunya disease typically presents with the fever-arthralgia-rash symptom triad. However, an increase in the number of atypical clinical manifestations, particularly neurological disorders, has occurred. The current evidence regarding the pooled prevalence of Chikungunya virus (CHIKV)-associated neurological cases (CANCs) suspected of having an arboviral aetiology is not well-understood. Therefore, this meta-analysis included 19 studies (n = 7319 patients) and aimed to determine the pooled rate of exposure to CANC. The pooled positivity rate of CANC was 12 % (95 % CI: 6–19), and Brazil was overrepresented (11/19). These estimations varied between 3 and 14 % based on the diagnostic method (real-time PCR vs. ELISA-IgM) and biological samples (cerebrospinal fluid or blood specimens) used for detection of CHIKV. Regarding the frequency of CHIKV in neurological clinical subgroups, the rates were higher among patients with myelitis (27 %), acute disseminated encephalomyelitis (27 %), Guillain–Barré syndrome (15 %), encephalitis (12 %), and meningoencephalitis (7 %). Our analysis highlights the significant burden of CANC. However, the data must be interpreted with caution due to the heterogeneity of the results, which may be related to the location of the studies covering endemic periods and/or outbreaks of CHIKV. Current surveillance resources should also focus on better characterizing the epidemiology of CHIKV infection in neurological disorders. Additionally, future studies should investigate the interactions between CHIKV and neurological diseases with the aim of gaining deeper insight into the mechanisms underlying the cause-and-effect relationship between these two phenomena.
Keywords: Atypical manifestation of chikungunya; Chikungunya virus; Illness severity mortality; Neuro-arboviruses; Neurological disorders